STUDY OF WINES POSITIONING ON THE ROMANIAN MARKET - Alex GAVRILESCU (Management & Marketing)
In this paper, I have done a research on the positioning of Romanian wines. The positioning is a necessary approach of brands to have a privileged position in the minds of consumers. In front of the keen foreign competition, the Romanian wine brands must assert a new identity to match the Romanian client's current lifestyle. The main objective of the research is the identification of the Romanian wine brand positioning. To achieve the objective of the research I have conducted a market research. The study was conducted on a sample of 100 respondents, consumers of Romanian wines. In the study, I have focused on a number of elements necessary for obtaining the positioning maps. Thus I tested the assisted and unassisted recognition of vineyards, the vineyards positioning depending on internal and international recognition and tradition / reputation, the vineyards positioning depending on the internal and international recognition and price, the vineyards positioning depending on sweet, red and light wines and on strong and dry wines. The positioning strategy will determine, on the one hand, the efficiency of the marketing activity at the level of consumer segment by obtaining a better image due to the high satisfaction of the specific needs, and on the other hand, the differentiation will enable to the company to gain competitive advantages, hence substantially increased profits. The theoretical contribution of this paper is to clarify the issues of positioning and to emphasize its importance. The practical contribution refers to the positioning of wines brands, which can be a model of reflection for each of the analyzed vineyards.